Tri‐Brominated Perovskite Film Management and Multiple‐Ionic Defect Passivation for Highly Efficient and Stable Solar Cells. Issue 4 (15th February 2021) - Gong, Zekun; He, Benlin; Zhu, Jingwei; Yao, Xinpeng; Wang, Sudong; Chen, Haiyan; Duan, Yanyan; Tang, Qunwei
Abstract : High‐quality perovskite films with low imperfections, high hole mobility, and matching energy levels play a crucial role in enhancing performance of perovskite solar cells (PSCs) without hole‐transporting materials (HTMs). Herein, it is demonstrated that the incorporation of a stable tetra‐bisphenol A (TBBPA) with diphenyl ring, polybromides, and hydroxyl groups additive into a perovskite film can simultaneously manipulate the crystal growth and passivate the defects through coordination interaction between the functional group (OH, Br) and the unsaturated halogen and metal ions (Br −, Cs +, and Pb 2+ ), resulting in a reduced grain boundary as well as imperfection and increased hole mobility of the CsPbBr3 perovskite film. In addition, the valence band of a perovskite film with TBBPA additive is shifted upward to approach the work function of the carbon electrode, thereby improving the energy level alignment. Consequently, a significantly boosted charge extraction and reduced charge recombination of the carbon‐based HTM‐free CsPbBr3 PSCs is obtained after incorporating the TBBPA additive, yielding a maximum power conversion efficiency of up to 9.82% of the optimized device. Furthermore, the champion PSC without encapsulation displays a remarkable thermal and moisture stability after being kept in ambient air for 720 h at 85 °C and 85% relative humidity, respectively. Abstract : The carbon‐based hole‐transporting material (HTM)‐free CsPbBr3 perovskite solar cell (PSC) achieves a maximized power conversion efficiency (PCE) of 9.82% with an excellent thermal and moisture stability through perovskite film management and multiple‐ionic defect passivation by the introduction of a tetra‐bisphenol A (TBBPA) additive.